IoT Piggy Bank for Money Saving Habit Instillation - Yee Wei, Eng; Bui Lin, Wee (UNIMAS Publisher, 2021)
Children nowadays are overwhelming with luxurious things and have only little or even no money concepts where most of the kids just reach out to their parents for buying anything they want. This could be an issue for parents, hence kids should be taught the value of money and knowing that save their own money is important to purchase anything they desired. This project proposed an innovative way to inculcate saving behaviours in children using an IoT Piggy Bank. This goal-directed approach allows children to set their saving goals (values of their desired items) and form a saving habit slowly through their saving routines toward their saving goals. Every saving made by the children will be tracked in a mobile app and a buzzer will be triggered as a reinforcer to alert children when they do not save regularly. The user acceptance testing (UAT) of the proposed prototype has shown the majority of the parents (90%) agreed that the proposed IoT piggy bank is very suitable for children to instil saving habit. Most of the children have reacted positively where they were having lots of fun when trying on the IoT piggy bank and expressed that they would continue to use it for saving in the future.